Change of direction asymmetry across different age categories in youth soccer - Trecroci, A.; Rossi, A.; dos Santos, T.; Formenti, D.; Cavaggioni, L.; Longo, S.; Iaia, F. M.; Alberti, G. (PeerJ, 2020)
Background: In youth, the development of change of direction (COD) and sprint performance is a key component for successfully competing in soccer across age. During a COD, the presence of directional asymmetries may be detrimental due to the unpredictable nature of the sport. Therefore, the aims of the study were to investigate asymmetries in COD ability and to examine the differences in COD and sprint performance across age in young soccer players.